2021
DOI: 10.3329/bjms.v20i5.55402
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of parents’ perceived stress and the parent-child relationship during the COVID-19 pandemic

Abstract: Objectives: The measures taken by governments to prevent the spread of COVID-19 have changed millions of people’s daily lives. This study analyzes parents’ perceived stress and parent–child relationship while staying home due to lockdown during the COVID-19 pandemic. Methods: The sample for this descriptive and cross-sectional study comprised 521 parents with children aged 4–18 years. Data were collected online using a Personal Information Form, the Perceived Stress Scale (PSS-4), and Child Parent Relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…37 People perceived increased stress, and anxiety that increases morbidity and mortality worldwide. [38][39][40][41] In this present study, comparing the fear score between the non-vaccinated and vaccinated groups, we found the vaccinated group having more fear compared to the non-vaccinated group although no significant difference was observed between the two (Table -5). The higher score in the vaccinated group correlates well with established behavioural theorisations of fear.…”
Section: Discussionmentioning
confidence: 42%
“…37 People perceived increased stress, and anxiety that increases morbidity and mortality worldwide. [38][39][40][41] In this present study, comparing the fear score between the non-vaccinated and vaccinated groups, we found the vaccinated group having more fear compared to the non-vaccinated group although no significant difference was observed between the two (Table -5). The higher score in the vaccinated group correlates well with established behavioural theorisations of fear.…”
Section: Discussionmentioning
confidence: 42%
“…In the process of monitoring and providing support, parents had a better understanding of their children’s education and appreciated the value of their children’s schooling. Tarsuslu et al (2021) reported that almost half of the parents in their sample in Turkey indicated that spending time at home with their children during the pandemic-induced school suspensions strengthened their relationships with their children and the majority of parents perceived that the time spent together at home with their children enabled them to take better care of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Stressors identified by Opanasenko et al include confinement, social and economic disruption, closure of schools and child care facilities as well as health anxiety 60 . Tarsuslu et al also highlight increasing stress among especially mothers and the parent-child relationship arising from lockdown measures 69 . The authors emphasise that there should be increased psychosocial support especially for mothers during pandemics to help address these concerns and challenges 69 .…”
Section: The Instigation Of Large Multi-arm Studies Including the World Health Organisation (Who) Solidaritymentioning
confidence: 99%
“…Tarsuslu et al also highlight increasing stress among especially mothers and the parent-child relationship arising from lockdown measures 69 . The authors emphasise that there should be increased psychosocial support especially for mothers during pandemics to help address these concerns and challenges 69 .…”
Section: The Instigation Of Large Multi-arm Studies Including the World Health Organisation (Who) Solidaritymentioning
confidence: 99%